International handbook of violence research - Heitmeyer, Wilhelm; Hagan, John, 1946- (Dordrecht ; Boston : Kluwer Academic Publishers, 2003)
The editors were delighted, therefore, by the cooperation and commitment shown by the eighty-one contributors from ten countries who were recruited to write on the sixty-two different topics, by the con- structive way in which any requests for changes were dealt with, and by the patient re- sponse to our many queries.
Preface. I: The Framework of the Handbook. 1. Violence: The Difficulties of a Systematic International Review W. Heitmeyer, J. Hagan. 2. The Concept of Violence P. Imbusch. 3. The Long-term Development of Violence: Empirical Findings and Theoretical Approach to Interpretation M. Eisner. II: Research on Violence: An Interdisciplinary Approach with a Focus on Social Sciences. 1. Societal Structures and Institutions: Social Conditions and State Agents. 1.1. Social Structures and Inequalities R.D. Crutchfield, T. Wadsworth, J.F. Short Jr., C. Hagemann-White. 1.2. Violence in and by State Institutions M. Hanagan, P. Longerich, G. Kummel, P. Klein, R.D. Crelinsten, J.-P. Brodeur. 2. Groups and Collectivities: Political and Ideological Violence. 2.1. Ethnopolitical Conflict and Separatist Violence T. Gurr, A. Pitsch. 2.2. Ethnic Violence A. Wimmer, C. Schetter. 2.3. The Socio-Anthropological Interpretation of Violence G. Elwert. 2.4. Civil Wars P. Waldmann. 2.5. Terrorism F. Reinares. 2.6. Violence from Religious Groups J. Pahl. 2.7. Vigilantism D. Kowalewski. 2.8. Pogroms W. Bergmann. 2.9. Violence and New Social Movements D. Ruscht. 2.10. Violence and the New Left D. della Porta. 2.11. Right-Wing Extremist Violence W. Heitmeyer. 2.12. Large-Scale Violence as Contentious Politics C. Tilly. 3. Violent Individuals: Perpetrators and Motives. 3.1. Processes ofLearning and Socialization J.T. Tedeschi, R.F. Baumeister, B.J. Bushman, E.V.E. Hodges, N.A. Card, J. Isaacs, H. Lukesch, H. Foster, J. Hagan. 3.2. Evolutionary and Social Biological Approaches M. Daly, M. Wilson, L. Baker, G. Albrecht, A. Blumstein, D. Hobbs, S. Messner. 4. Victims of Violence: Individuals and Groups. 4.1. Violence against Children J. Gabarino, C.P. Bradshaw. 4.2. Violence in Intimate Relationships P. Russell, R. Dobash, R.E. Dobash. 4.3. Suicide D. Lester. 4.4. Violence against the Socially Expendable E.A. Fattah. 4.5. Violence against Ethnic and Religious Minorities T. Bjorgo. 4.6. Hate Crimes Directed at Gay, Lesbian, Bisexual and Transgendered Victims J. McDevitt, J. Williamson. 4.7. Trauma and Violence in Children and Adolescents: A Developmental Perspective B.A. van der Kolk, A. Streeck-Fischer. 5. Social Opportunity Structures: Institutions and Social Spaces. 5.1. Violence in Social Institutions R.J. Gelles, G. Klewin, K.J. Tillmann, G. Weingart, V. di Martino, E. Dunning. 5.2. Violence in the Public Space R. Koelbel, F. Dubet. 6. Violence Discourses: Ideologies and Justifications. 6.1. Discourses and Ideologies T. Meyer, H. Munkler, M. Llanque, K. Burgess-Jackson, V. Krech, J. Nieraad. 6.2. Justification Strategies D. Grimm, A. Funk, O. Backes, P. Reichenbach, H. Bielefeldt, S. Lamnek. 7. Processes and Dynamics: Escalation and De-Escalation. 7.1. Fear of Violent Crime K. Boers. 7.2. Public Opinion and Violence H.M.
Includes bibliographical references and index.
Keywords: Violence; Violence -- Research -- Handbooks, manuals, etc